Health‐related quality of life in patients with metastatic basal cell carcinoma treated with cemiplimab: Analysis of a phase 2 trial - Ketty Peris; Timothy J. Inocencio; Alexander J. Stratigos; Karl D. Lewis; Zeynep Eroglu; Anne Lynn S. Chang; Cristina Ivanescu; Aleksandar Sekulic; Matthew G. Fury; Chieh‐I Chen; Ruben G. W. Quek (Cancer Medicine)
Abstract Background A phase 2 cemiplimab study (NCT03132636) demonstrated a 24.1% objective response rate in patients diagnosed with metastatic basal cell carcinoma (mBCC) who were not candidates for continued hedgehog inhibitor (HHI) therapy due to intolerance to previous HHI therapy, disease progression while receiving HHI therapy, or having not better than stable disease on HHI therapy after 9 months. Here, health‐related quality of life (QoL) for this patient population is reported. Methods Adult patients with mBCC were treated with intravenous cemiplimab at a dose of 350 mg every 3 weeks for 5 treatment cycles of 9 weeks/cycle then 4 treatment cycles of 12 weeks/cycle. Patients completed the European Organisation for Research and Treatment of Cancer Quality of Life‐Core 30 (QLQ‐C30) and Skindex‐16 questionnaires at baseline and Day 1 of each cycle. Across Cycles 2 to 9, the overall change from baseline was analyzed using a mixed model with repeated measures. Responder analyses determined clinically meaningful improvement or deterioration (changes ≥10 points) or maintenance across all scales. Results Patients reported low symptom burden and moderate‐to‐high functioning at baseline. Maintenance for QLQ‐C30 global health status (GHS)/QoL and across all functioning and symptom scales was indicated by overall mean changes from baseline. Clinically meaningful improvement or maintenance was reported at Cycle 2 for GHS/QoL (77%), functioning scales (77% to 86%), and symptom scales (70% to 93%), with similar proportions of improvement or maintenance at Cycles 6 and 9, excluding fatigue. On the Skindex‐16, clinically meaningful improvement or maintenance was reported across the emotional, symptom, and functional subscales, in 76%–88% of patients at Cycle 2, which were generally maintained at Cycles 6 and 9. Overall mean changes from baseline showed maintenance across these subscales. Conclusions The majority of patients treated with cemiplimab reported improvement or maintenance in GHS/QoL and functioning while maintaining a low symptom burden.